ANALISIS IMPLEMENTASI DECISION SUPPORT SYSTEM (DSS) UNTUK PENGAMBILAN KEPUTUSAN DI INSTITUSI PENDIDIKAN - Yulita, Peni; Pujianti, Ninit; M, Sufyarma; Irsyad, Irsyad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
A Decision Support System (DSS) is a computer-based system that supports decision-making by integrating data, information, and analytical models. The implementation of DSS is increasing in educational institutions due to the complexity of educational management, which demands precision, speed, and accuracy in decision-making. This study uses a literature review method by comprehensively analysing a number of scientific articles, books, research reports, and international publications from the last 10 years. The main focus of the study is to analyse the application of DSS in educational institutions, its benefits in supporting strategic decisions, implementation challenges, and its implications for educational governance. The results show that DSS can improve managerial efficiency, the quality of educational services, academic data management, budget planning, scheduling, and support data-based policies. However, technical challenges such as a lack of user competence, minimal digital infrastructure, and data integration are major obstacles to DSS implementation. This study concludes that the successful implementation of DSS requires technological readiness, human resource competency, policy support, and strong data governance.